Account-Making Following Relationship Dissolution: Exploring Sex as a Moderator in Public and Private Breakup Accounts. Issue 3 (15th March 2020) - LeFebvre, Leah E.; Brody, Nicholas; Blackburn, Kate G.
ABSTRACT: This study examines sex differences in emotion word use in retrospective private and public relationship dissolution accounts through two studies. Study 1 ( n = 423) found men's use of negative emotion words in private breakup accounts correlated with their use of negative emotion words in their public accounts; however, women's emotion words in their private breakup accounts did not correlate with their use of emotion words in their public accounts. Study 2 ( n = 284) replicated Study 1 with a broader sample and revealed the same pattern of negative emotion word use. These studies suggest that after a breakup women and men may process emotions differently in their public and private breakup accounts depending on their audience. The findings offer insights into how relationship dissolution model processes, evolutionary mating strategies, and self-presentation may influence linguistic variations accounting for sex differences.